Consecutive days of racing does not affect sleep in professional road cyclists - Sargent, C.; Halson, S. L.; Martin, D. T.; Roach, G. D. (International Journal of Sports Physiology and Performance, 2022)
Purpose: Professional road cycling races are physiologically demanding, involving successive days of racing over 1 to 3 weeks of competition. Anecdotal evidence indicates that cyclists` sleep duration either increases or deteriorates during these competitions. However, sleep duration in professional cyclists during stage races has not been assessed. This study examined the amount/quality of sleep obtained by 14 professional cyclists competing in the Australian Tour Down Under.